Truncated nonsmooth Newton multigrid methods for block-separable minimization problems - Gräser, Carsten; Sander, Oliver (IMA Journal of Numerical Analysis, 2019)
The Truncated Nonsmooth Newton Multigrid method is a robust and efficient solution method for a wide range of block-separable convex minimization problems, typically stemming from discretizations of nonlinear and nonsmooth partial differential equations. This paper proves global convergence of the method under weak conditions both on the objective functional and on the local inexact subproblem solvers that are part of the method. It also discusses a range of algorithmic choices that allows to customize the algorithm for many specific problems. Numerical examples are deliberately omitted, because many such examples have already been published elsewhere.
CRIS-Team Scopus Importer:2022-03-23
Keywords: Block separable; Convex minimization; Global convergence; Multigrid